ОҚЫТЫЎ ПРОЦЕСИНДЕ БАЛАНЫ ЖЕКЕ АДАМ СЫПАТЫНДА ҚӘЛИПЛЕСТИРИЎ МӘСЕЛЕЛЕРИ - Уразимова, Т.В. (SCIENCE and SOCIETY, 2016)
The article is dedicated to modern contents of spiritual-creative education of children of preschool age because attention increased in modern society to the problem forming all-round developed, spiritual rich and creative personalities. The personality of a man, his spiritual and moral look are formed, first of all, in the process of the education. So the process of education is necessary to found on making the conditions for upbringing the creative personality ready to dialogue, cooperation and creative activity in different spheres of the life.
Keywords: Pedagogics; social sphere; education process; methodology; education methods; education; creativity